Edukasi Aktivitas Fisik Pada Ibu Hamil Dengan Media Video Aktivitas Fisik Dan Poster Aktivitas Fisik - Fatmarizka, Tiara; Priambodo, Hafid Dito; Deistriany, Zehra Karil; Andriawan, Wahyu; Nadhirah, Sabina Azka; Jamil, Layla Widad; Pristianto, Arif (Universitas Gajah Putih, Indonesia, 2023)
Physical activity is any type of body movement that involves the working of the body's muscles and increases energy consumption in the body. Physical activity in pregnant women is very important to do so that the health of the mother and fetus is maintained. Based on observations that have been made in Pucangan Village, the most common problem is the lack of awareness for physical activity among pregnant women. This is what prompted us to conduct education about the physical activity of pregnant women in the Pucangan Village Pregnant Women Class, providing this education using physical activity video and physical activity posters media so that it can be easily accepted by pregnant women. The contents of the material that we provide are physical activities that pregnant women can do at home. Where pregnant women understand about physical activities that can be done such as gymnastics even though, not only that physical activity can also be in the form of housework which includes: sweeping, washing dishes, shopping for daily needs, and exercising with a gymball. We also distributed a pre test before giving the material and a post test after giving the material. We provide pre test and post test as indicators of the success of this activity. The results of the pre test and post test show that the knowledge about physical activity in pregnant women has increased from not really understand to understand. With the education in the class for pregnant women in Pucangan Village, we hope that the participants can implement it into their daily activities so that they can meet the physical activity needs of pregnant women.